Influences of motivation on sales performance: A study of life insurance agent in Kota Kinabalu - Liaw, Milin (2006)
Based on Vroom's Theory, this research discusses the application of a motivational model that provides a practical tool for life insurance agent. The motivational models are Expectancy, Instrumentality and Valence. A sample of Life insurance agent from Kata kinabalu has been taken as samples for the research and they are required to identify which variables were significant influences their motivation to perform well. All level of employees from agent to agency manager involved in this research. The finding of this research determined that all the motivation model (expectancy, instrumentality and valence) were significant influenced of motivation on performance by simple linear regression, but when the model were correlated together into multiple regression for the purpose of identifying the best-fitting model, researcher found out that valence model was the most contributed influences of motivation on performance followed by instrumentality. Expectancy model also gave significant but opposite significant if tested through multiple regressions. Then, when the three models are moderated with age, gender and education, author found that only gender shown significant influenced to expectancy and instrumentality. Levels of education (graduated and non graduated) gave significant to the instrumentality model. Others moderating variables were not shown any significant influenced of motivation on performance. As conclusion, author has recommended that the best influenced of motivation on performance was valence. This valence should be offered continuously to the life insurance agent for high performance. But, the valence model could be applied similarly with expectancy and instrumentality models since both of this can be moderated with gender and education. This research only based on individual research. Further studies are advised to develop other motivation model in order to determine others significant influences motivation on performance especially for sales force.